Brain-enriched miR-128: Reduced in exosomes from Parkinson’s patient plasma, improves synaptic integrity, and prevents 6-OHDA mediated neuronal apoptosis - Bhattacharyya, Pallabi; Biswas, Atanu; Biswas, Subhas C. (Frontiers in Cellular Neuroscience, 2023)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder associated with death of dopaminergic neurons. Unfortunately, no effective cures or diagnostic biomarkers for its detection are available yet. To address this, the present study focuses on brain-enriched small non-coding regulatory RNAs called microRNAs (miRNAs) that are released into the circulation packaged inside small extracellular vesicles called exosomes. We collected blood samples from a PD patient cohort and isolated exosomes from the plasma. qPCR-based detection revealed a particular neuron-enriched miR-128 to be significantly decreased in the patient-derived exosomes. Interestingly, a concomitant decreased expression of miR-128 was observed in the cellular models of PD. Fluorescent live cell imaging and flow-cytometry revealed that over-expression of miR-128 can prevent 6-OHDA-mediated mitochondrial superoxide production and induction of neuronal death respectively. This neuroprotective effect was found to be induced by miR-128-mediated inhibition of FoxO3a activation, a transcription factor involved in apoptosis. miR-128 over-expression also resulted in down-regulation of pro-apoptotic FoxO3a targets- FasL and PUMA, at both transcript and protein levels. Further downstream, miR-128 over-expression inhibited activation of caspases-8, -9 and -3, preventing both the intrinsic and extrinsic pathways of apoptosis. Additionally, over-expression of miR-128 prevented down-regulation of synaptic proteins- Synaptophysin and PSD-95 and attenuated neurite shortening, thereby maintaining overall neuronal integrity. Thus, our study depicts the intracellular mechanistic function of neuroprotective miR-128 and its implications as a biomarker in the circulating exosomes detectable in PD patient blood. The characterization of such exosomal brain-enriched miRNAs could be the key to effective diagnosis of degenerative brain disorders like PD.